Negotiating climate change: Science, policy, and the invisible power embedded in public discourse in Chinese social media - Kaijiao Zhang; Bingkang Qu; Qizhi Huang (PLoS ONE, 2026)
The use of social media has enabled diverse actors to engage in climate discourse, shifting climate change from a purely scientific issue to a broader global risk topic. Drawing on a decade of data from the Chinese platform Zhihu, this study employs social network analysis and correspondence analysis to examine the structural characteristics and phased evolution of social representations of climate change. The findings indicate that public discussions consistently anchor climate change in scientific evidence, forming a relatively stable core system. However, its peripheral structure has undergone continuous adjustment and expansion through the interaction between policy contexts and public communication, shifting from an emphasis on scientific consensus toward risk governance and economic pathways. This structural configuration reflects the dialogical and polyphasic nature of knowledge, while the economic perspective has emerged as a dominant representation of climate change in the Chinese context. This demonstrates the ongoing restructuring of social representations of climate change under the influence of policy and ideology, which may have significant implications for the public's perception of risk.